Pengembangan Standar Operasional Prosedur (SOP) Pelaksanaan Tugas Pendidik dan Tenaga Kependidikan di SMK Islam Terpadu (IT) Cahaya Peradaban Kabupaten Lima Puluh Kota - Dilla Gusti Elfira; Silfia Hanani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study is motivated by issues in the quality of school management at SMK IT Cahaya Peradaban, particularly concerning inefficiencies in the execution of duties by educators and education personnel. The problems stem from a lack of structured documentation, unclear responsibilities, and overlapping tasks, resulting in low work efficiency and difficulty in performance measurement. The aim of this research is to develop a Standard Operating Procedure (SOP) that is valid, practical, and effective in improving the quality of task execution within the school environment. The research method used is Research and Development (R&D), involving stages such as problem identification, SOP development based on literature and expert input, validation by expert validators, revision, user training, field testing, and dissemination of results. The findings reveal that the developed SOP is highly valid (average score 4.26), highly practical (average score 4.29), and highly effective (effectiveness score 89.63). The SOP provides a clear, structured, and applicable guide for daily task implementation. Its implementation is expected to enhance work efficiency, reduce task overlaps, and improve overall school governance.